ANALISIS PENGARUH PENGUMUMAN DIVIDEN TERHADAP PERUBAHAN HARGA SAHAM (RETURN) SEBELUM DAN SESUDAH EX-DIVIDEND DATE DI BURSA EFEK JAKARTA (BEJ) - Wibowo Wibowo; Melati Adorini (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2006)
The objective of this research was to analyze the impact of ex-dividend date announcement in Jakarta Stock Exchange (JSX) on stock return during the period of 2000- 2004. This research takes 25 corporation samples which are divided into two groups, namely increasing dividend group and decreasing dividend group. The method used in this research is event study that observed the stock return movement in capital market. The observation period was during 15 days before and 15 days after ex-dividend date. In order to examine the existence of price reaction, the abnormal return was conducted during the event period towards the increasing dividend group and decreasing dividend group. The independent variable used was dividend declaration (increasing dividend and decreasing dividend) and dependent variable used was stock return. The calculation of this research using paired sample t test, was to prove if there is any stock return differences between before and after ex-dividend date announcement with the presence of increasing dividend declaration and decreasing dividend declaration in Jakarta Stock Exchange (JSX). The result of this research had shown two conclutions that for the increasing dividend group, there were no stock return (abnormal return) diffrerence between before and after ex-dividend date due to the increasing dividend declaration in Jakarta Stock Exchange (JSX) and for the decresing dividend group there was stock return (abnormal return) difference between before and after ex-dividend date due to decresing dividend declaration in Jakarta Stock Exchange (JSX).